Efek Pemberian Vitamin E (d-α-tocopherol) terhadap Memori Kerja Spasial Tikus (Rattus novergicus) Remaja yang Diinduksi Etanol - Shera Nadhila Setyo Bisono; M. Ihwan Narwanto; Kristianningrum Dian Sofiana (Pustaka Kesehatan, 2014)
During neurogenesis process, nerve cells especially hippocampus susceptible to damage when exposed to ethanol. Vitamin E is an antioxidant and capable to protect nerve cells damage. This study aimed to determine the effect of vitamin E (d-α-tocopherol) on spatial working memory of adolescent rats induced with ethanol. The study used 30 days-old rats (Rattus novergicus), weight between 50-100 grams. Total of 25 rats were divided into 5 groups: 2 control groups and 3 treatment groups. K1/K(-) was normal group without ethanol and vitamin E, and K2/K(+) were induced with ethanol. The treatment groups were given ethanol and vitamin E at a dose of 100mg/kgBW; 200 mg/kgBW; 400 mg/kgBBW respectively for P1, P2 and P3. After treatment for 14 days, the rats were tested for spatial working memory using the Radial Arm Maze (RAM) for 10 consecutive days. Spatial working memory was observed by the total number of right arm option which were entered by rats. The average number of right arm maze option for 10 days, were; K (-): (7 ± 0.52), K (+): (3.98 ± 0.66), P1: (4 , 56 ± 0.41), P2: (6.76 ± 1.01) and P3 (6.38 ± 0.63). In conclusion, there was an effect of vitamin E at a dose of 200 mg/kgBW and 400 mg KgBW on spatial working memory of ethanol-induced adolescent rats.   Keywords: ethanol, vitamin E, spatial memory, Radial Arm Maze